PENGARUH INDEPENDENSI, KEAHLIAN PROFESIONAL, DAN PENGALAMAN KERJA PADA KINERJA PENGAWAS KOPERASI SERBA USAHA - Prawitasari, Putu Putri; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2015)
This study aims to determine the effect of independence, professional skills and work experience in supervisory performance KSU in the District of East Denpasar. This study uses 40 samples were determined based on the guidelines of Roscoe (1982) in Sugiyono (2012). Respondents were KSU chairman and supervisor in the District of East Denpasar population numbering as many as 404 people. Data collection methods used in this study is the documentation and questionnaires. Multiple linear regression analysis is used as a data analysis technique. The results of this study indicate that the independence, professional skills, work experience and a significant positive effect on the performance of the supervisory KSU in East Denpasar. It shows that the higher the independence, professional skills, and work experience, the higher the performance results of the supervisor.
Keywords: Supervisors, Performance, Independence, Professional Skills, Work Experience